2011
DOI: 10.4103/2156-7514.92186
|View full text |Cite
|
Sign up to set email alerts
|

Adenomatoid Odontogenic Tumor – A Report of Two Cases with Histopathology Correlation

Abstract: Adenomatoid odontogenic tumor (AOT) is an uncommon, hamartomatous, benign, epithelial lesion of odontogenic origin that was first described by Driebaldt in 1907, as a pseudo-adenoameloblastoma. The current World Health Organisation (WHO) classification of odontogenic tumors defines AOT as being composed of the odontogenic epithelium in a variety of histoarchitectural patterns, embedded in mature connective tissue stroma, and characterized by slow, but progressive growth. The current article reports two cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 5 publications
(6 reference statements)
1
22
0
5
Order By: Relevance
“…However, most authors accept its odontogenic source as it occurs within the tooth bearing areas of the jaws and is often found in close association with impacted teeth. There is evidence that the tumour cells are derived from enamel organ epithelium; investigators have also suggested that the lesion arises from remnants of dental lamina 27 . As the histogenesis is still uncertain, there has long been a debate as to whether it represents a hamartomatous growth or a true benign neoplasm, having cytological features similar to various components of enamel organ, dental lamina and reduced enamel epithelium 6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, most authors accept its odontogenic source as it occurs within the tooth bearing areas of the jaws and is often found in close association with impacted teeth. There is evidence that the tumour cells are derived from enamel organ epithelium; investigators have also suggested that the lesion arises from remnants of dental lamina 27 . As the histogenesis is still uncertain, there has long been a debate as to whether it represents a hamartomatous growth or a true benign neoplasm, having cytological features similar to various components of enamel organ, dental lamina and reduced enamel epithelium 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Adenomatoidni odontogeni tumor se može javiti intraosealno i ekstraosealno 27 . Intraosealni AOT ima ekpanzivni rast i može biti radiografski podeljen na dva tipa: folikularni (perikoronarni) i ekstrafolikularan (ekstrakoronarni).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…It is usually associated with impacted teeth, most commonly the canine [7][8] . It mainly affects females, in a ratio of 1.9:1, and this preference is even higher in the Asian population, the highest incidence being in Sri Lanka (3.2:1) and Japan (3:1) 9 .…”
Section: Discussionmentioning
confidence: 99%